2017
DOI: 10.1007/s00726-017-2448-8
|View full text |Cite
|
Sign up to set email alerts
|

Single and chronic l-serine treatments exert antidepressant-like effects in rats possibly by different means

Abstract: In the present study, the effects of both single (6 mmol L-serine/10 ml/kg orally administrated) and chronic (2% L-serine solution freely given for 28 days) treatments on depression-like behavior were evaluated in Wistar rats, representing the control, and Wistar Kyoto rats, representing an animal model of depression. Both single and chronic L-serine treatments decreased the duration of immobility, which is an index of a depressive-like state, in the forced swimming test in both strains. However, the decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In addition, in the case of acute treatment, the concentration of L-Ser in plasma was found to have increased eightfold 30 min after the oral administration, and that in the hippocampus and the cortex also increased [ 25 ]. On the other hand, as has been reported in previous research using rats [ 17 ], chronic treatments do not affect L-Ser levels in the plasma and brain. Thus, there is a broad difference in metabolism and behaviors between single and chronic L-Ser treatments.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, in the case of acute treatment, the concentration of L-Ser in plasma was found to have increased eightfold 30 min after the oral administration, and that in the hippocampus and the cortex also increased [ 25 ]. On the other hand, as has been reported in previous research using rats [ 17 ], chronic treatments do not affect L-Ser levels in the plasma and brain. Thus, there is a broad difference in metabolism and behaviors between single and chronic L-Ser treatments.…”
Section: Discussionsupporting
confidence: 75%
“…The reduction might have been caused by changes in the brain levels of D-Ser, a metabolite of L-Ser, which suppresses intake of high-preference food [ 23 ]. In rats chronically supplemented with L-Ser, D-Ser levels in the brain increased, while L-Ser in the brain, as well as L-Ser and D-Ser in the plasma, did not increase [ 17 ]. These data are comparable with our data showing the concentration of L-Ser in plasma not to have changed.…”
Section: Discussionmentioning
confidence: 99%
“…S5). A previous study showed that chronic L-serine treatments exert antidepressant-like effects on Wistar Kyoto rats 33 . The discrepancy between our study and the previous report might be due to the differences in animal models.…”
Section: Fluoxetine Stimulates Rankl Secretion By Bmas Through Cox-2/mentioning
confidence: 96%
“…The release of d -serine can be triggered by glutamate [39], so a reduced glutamate level might lessen the release of serine in our present study. The antidepressant effects of acute and chronic d -serine or l -serine treatment have been investigated in serotonin depletion, learned helplessness, and the OBX paradigm [37,39,40]. Sarcosine, also as a co-agonist of NMDAR, could alleviate depressive symptoms in patients and reverse behavioral deficits in CUMS-induced animals, and its antidepressant effects were superior to citalopram [41].…”
Section: Discussionmentioning
confidence: 99%